Packaging film containing anti-fog agent

JP7668827B2Active Publication Date: 2025-04-25NOVAMONT SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022579882
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-23
Filing Date
2021-06-23
Publication Date
2025-04-25
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

Biodegradable polyester films with anti-fogging properties often fail to meet the requirements for mechanical properties, aging stability, and compatibility with packaging machinery, leading to issues such as hazing, reduced transparency, and poor unwindability.

Method used

Incorporation of specific antifog agents like esters of polyfunctional alcohols, such as polyglyceryl laurate and sorbitan monolaurate, into biodegradable aliphatic and aliphatic-aromatic polyesters, with controlled molecular weights and friction coefficients, enhances mechanical properties and compatibility with packaging machinery.

Benefits of technology

The films exhibit improved transparency, unwindability, and performance in packaging machines, maintaining mechanical strength and anti-fogging capabilities over time, suitable for food and industrial packaging.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A packaging film having a static friction coefficient greater than 5, the packaging film having a melt strength of 0.7 to 4 g, and comprising: (i) at least one dicarboxylic acid unit and at least one diol unit; and (ii) an anti-fog agent selected from an ester of a polyfunctional alcohol (provided that the ester is not a stearate).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a biodegradable packaging film comprising a biodegradable polyester and an anti-fog agent. [Background technology]

[0002] Packaging films are known from the trade and literature. Typically, these films are 3 to 50 μm thick and are used, for example, to package food products before they are placed in the refrigerator or packed into containers. Achieving an optimal packaging film is not easy, as its use requires many special technical characteristics, such as:

[0003] -sticky The film has the basic property of adhering to both itself and other non-adhesive surfaces without the addition of adhesives, which allows the user of such a film to wrap one or more layers of film around an object (e.g., food on a plate), thus hermetically sealing the object. -Transparency An essential feature is transparency, which allows the user of such films to identify objects packaged therein without having to unpack such objects. From a commercial perspective, it is highly desirable that products packaged in the film be as clearly visible as possible, and therefore it is particularly important that the film does not dull over time. -Mechanical properties Mechanical properties are the physical characteristics that give the packaging material its mechanical performance and strength. Specifically, we measure tensile strength (MPa), elongation at break (%), and modulus of elasticity (MPa) in both the machine direction (MD) and the transverse direction (TD).

[0004] -Shelf life It is essential to use polyesters that give the film good ageing stability to ensure that the product is kept as long as possible, in any case at least up to 6 months and preferably up to 1 year. -Rewind While adhesive ability is important, excessive adhesiveness can make the film difficult to unwind, both industrially and in end-use applications, and can lead to film breakage during packaging. Ease of unwinding is a crucial property for use on industrial packaging machinery. -Anti-fog The anti-fogging property is a feature that is particularly valued in the marketplace: it avoids the micro-condensation of moisture that causes fogging in the packaging of fresh and refrigerated products, typically meat and vegetable products. -Film suitability for packaging machines Films must meet the correct requirements to enable the production of thin, elastic films for use in automated packaging (wrapping) machines. In this application, the "smoothness" of the film on moving parts is particularly important, requiring special setup procedures to improve the film's performance in the packaging machine.

[0005] Therefore, there is a particular need for films made from biodegradable polyesters that optimize the above properties. The use of anti-fog properties in polymeric films is widely known in the art. WO2019012564A1 describes a plasticized PVC stretch film containing an ester-based plasticizer of renewable origin, polyester, and natural oil, and the film further contains an anti-fog agent, typically a fatty acid ester. WO2019012564A1 points out the technical drawback that biodegradable polyester films with anti-fog properties do not meet the special characteristics and correct requirements for producing thin, flexible films for use in automatic packaging machines (wrapping machines). In this application, the "stickiness" of the film on moving parts is particularly critical, requiring special setup work that inevitably impairs the film's performance in the packaging machine to an unacceptable extent.

[0006] EP 2550330 A1 describes a polymer blend, a cling film and a method for obtaining the same, specifically a film comprising an aliphatic polyester with a low aromatic content. EP2499189B1 describes a method for producing a multilayer film comprising 45-70 wt% aliphatic-aromatic polyester, 30-55 wt% PLA, with a blow-up ratio of 4:1 or less, wherein at least the core layer comprises 20-70% w / w aliphatic-aromatic polyester, 30-80 wt% PLA.

[0007] EP 2 331 634 B1 discloses biodegradable polymer mixtures containing 40 to 95% by weight of an aliphatic or aliphatic-aromatic polyester, 5 to 60% by weight of a polyalkylene carbonate, in particular polypropylene carbonate, and 0.1 to 5% by weight, based on the sum of the two components, of a copolymer containing epoxy groups based on styrene, acrylic esters and / or methacrylic esters. The possibility of using antifogging agents is mentioned in all these patents.

[0008] In patents IT102020000012184 and EP2632970, the applicant describes biodegradable polyesters that are particularly suitable for use in the manufacture of films, comprising units derived from at least one diacid and at least one diol, and characterized by a static coefficient of friction greater than 5 and greater than 10, respectively. Summary of the Invention [Problem to be solved by the invention]

[0009] Surprisingly, it has been found that the addition of anti-fog agents to biodegradable polyesters used to produce films with a static friction coefficient above 5, preferably above 10, results in a synergistic effect that endows these films with the well-known improved anti-fog ability, as well as better unwinding and sometimes even improved transparency properties, while keeping the mechanical properties and aging stability substantially unchanged. Surprisingly, these films can also be optimally adapted to food tray packaging machines.

[0010] The use of anti-fog agents in films made from biodegradable polyesters is not easy or obvious, because anti-fog agents are not always compatible with polyester itself.In many cases, anti-fog agents may simply not provide the desired anti-fog function, while in other cases, anti-fog agents may cause the formation of powder on the surface of the film, which makes the film cloudy, less transparent, and reduces the desired adhesive ability.In addition, there is a technical prejudice in the art that it is claimed that films made from biodegradable polyesters containing anti-fog agents are disadvantageous for their use in industrial packaging machines, making their use economically unviable.

[0011] Therefore, it is particularly desirable to find specific anti-fog agents for films made from biodegradable aliphatic and aliphatic-aromatic polyesters. Therefore, suitable anti-fog agents have been selected to solve the above technical problems. [Means for solving the problem]

[0012] Therefore, one aspect according to the present invention is (i) having a melt strength of 0.7 to 4 g and containing at least one dicarboxylic acid unit and at least one diol unit; Mn≧40000 Mw / q≦90000 A biodegradable polymer having the formula: Melt strength is measured according to ISO 16790:2005 at 180°C and γ=103.7s -1 , using a capillary with a diameter of 1 mm and L / D=30, 2 Measured at a constant acceleration of 110 mm and an extension length of 110 mm. Molecular weights "Mn" and "Mw" are determined by gel permeation chromatography (GPC); "q" = weight percentage of polyester oligomers having a molecular weight of 10,000 or less as measured by GPC; and (ii) an anti-fog agent selected from esters of polyfunctional alcohols (provided that the esters are not stearates), preferably condensation products of polyfunctional alcohols with fatty acids, present in an amount of 0.2 to 5%, preferably 1 to 3%, relative to the polyester content; and a packaging film having a thickness of 3 to 50 μm, preferably 6 to 25 μm, and having a coefficient of static friction (COF) of greater than 5, preferably greater than 10. More preferably, the anti-fog agent is present in an amount of 1.0 to 2.0%, and even more preferably in an amount of 1.0 to 1.5%.

[0013] With regard to ISO 16790:2005, according to said standard, melt strength values ​​are expressed in Newtons. However, in the text and examples, for ease of reading, melt strength values ​​are expressed as "gram force" according to the following conversion: 1N = 102 g force; 1cN = 1.02 g force. Thus, data obtained in Newtons are converted to grams force by multiplying the obtained value by 0.0098.

[0014] The antifogging agents according to the invention are selected from esters of polyfunctional alcohols (provided that said esters are not esters of stearic acid), preferably condensation products of polyfunctional alcohols with one or more fatty acids and their ethoxylated derivatives. Suitable compounds which may be used as antifogging agents are therefore polyglyceryl laurate, sorbitan monooleate, sorbitan trioleate, glycerol monopalmitate and sorbitan polyoxyethylene monolaurate esters. In a preferred embodiment of the invention, the antifogging agent is selected from esters of fatty acids having from 8 to 18 carbon atoms, more preferably from 12 to 16 carbon atoms. In a particularly preferred embodiment of the invention, the fatty acid ester is selected from polyglyceryl laurate and sorbitan monolaurate.

[0015] In the present invention, with respect to the antifogging agent, "ester" means either a pure ester or a mixture of esters (two or more individual esters different from each other). The esters characterizing the antifogging agents according to the invention comprise at least 20%, preferably 30%, and even more preferably 60% by weight of partial esters of polyfunctional alcohols relative to the ester itself, and in some cases it has been found that the partial esters of polyfunctional alcohols or condensation products of polyfunctional alcohols with fatty acids account for up to 80% or 90% by weight of the ester.

[0016] The anti-fog agent can be added to the polyester directly to the desired final concentration by extrusion, or in the form of a "masterbatch" in a hopper during the film-forming step. In this invention, "masterbatch" refers to polyester pellets containing a high concentration of the anti-fog agent. The concentration of the additive in the masterbatch is usually 10%. Preferably, the film antifog agent according to the present invention is biodegradable according to the criteria set out in standard EN 13432. More preferably, the antifog agent undergoes 10-60% biodegradation in a 10 day time window within a 28 day test according to OECD method 301B. Polyesters which can be used to manufacture the films according to the invention are those of the aforementioned patents IT102020000012184 and EP2632970 in the name of the Applicant, to which reference is made for the characteristics of the polyesters and the methods for their manufacture.

[0017] As far as the coefficient of static friction (COF) is concerned, it represents the resistance of a material to sliding. For films, the coefficient of static friction is determined in accordance with the revised version of ASTM standard D1894 "Static and kinetic coefficients of friction of plastic films and sheets." Therefore, in the present invention, the coefficient of static friction is measured as follows: A film sample, 3 to 50 μm thick, preferably 6 to 25 μm thick, is wrapped around a glass plate support surface approximately 150 × 300 mm × 2 mm thick. The film sample must adhere completely to the glass plate, with a smooth, wrinkle-free surface. To achieve this, a brush can be used to apply moderate pressure to remove any air bubbles that may have formed between the film and the glass plate. The glass plate is placed horizontally, and a 200 ± 5 gram weight, 63.5 × 5 mm thick stainless steel sled is placed on top of it. Moderate pressure is applied to the surface by hand to improve adhesion of the sled to the film surface. A load cell is connected to one end of the sled with nylon filament. The load cell is placed on the movable crossbar of the dynamometer. The load cell can be moved at a constant speed of 10 mm / min. The static friction coefficient is defined as the ratio of the force (F) recorded by the dynamometer at the moment the thread no longer adheres to the film (the tangential frictional force opposing sliding) to the weight (Fg) acting perpendicular to the two contact surfaces (the weight of the steel thread).

[0018] Preferably, the polyester used in the production of adhesive films according to the present invention has a gel fraction of less than 5%, more preferably less than 3%, and even more preferably less than 1%. The gel fraction is determined by placing a sample of polyester (X1) in chloroform, filtering the mixture through a 25-45 μm sieve, and measuring the weight of the material (X2) remaining on the filtration screen. The gel fraction is determined as the ratio of the weight of the material thus obtained to the weight of the sample, i.e., (X2 / X1) × 100.

[0019] The polyesters are advantageously chosen from biodegradable aliphatic and aliphatic-aromatic polyesters, with aliphatic-aromatic polyesters being particularly preferred. Aliphatic polyesters are derived from at least one aliphatic dicarboxylic acid and at least one aliphatic diol. As for the aliphatic-aromatic polyesters, they have an aromatic portion mainly constituted by at least one polyfunctional aromatic acid and an aliphatic portion comprising at least one aliphatic dicarboxylic acid and at least one aliphatic diol. Polyfunctional aromatic acids are dicarboxylic aromatic compounds of the phthalic acid type and their esters, as well as heterocyclic dicarboxylic aromatic compounds of renewable origin and their esters. Particularly preferred are 2,5-furandicarboxylic acid and its esters, and terephthalic acid and its esters, and mixtures thereof.

[0020] Aliphatic dicarboxylic acids refer to dicarboxylic acids having 2 to 22 carbon atoms in the main chain and their esters. Dicarboxylic acids from renewable sources, their esters, and mixtures thereof are preferred, among which adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, undecanedioic acid, dodecanedioic acid, brassylic acid, and mixtures thereof are preferred. In a particularly preferred embodiment, the aliphatic dicarboxylic acids of the biodegradable polyester for producing the anti-fog film according to the present invention comprise at least 50 mol % of azelaic acid, sebacic acid, adipic acid, or mixtures thereof, based on the total moles of aliphatic dicarboxylic acids. Also included are dicarboxylic acids with in-chain unsaturation, such as itaconic acid and maleic acid.

[0021] In the polyesters used according to the invention, diols are understood to be compounds having two hydroxyl groups. Aliphatic diols of C2 to C13 are preferred. Examples of aliphatic diols include 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, 2-methyl-1,3-propanediol, dianhydrosorbitol, dianhydromannitol, dianhydroiditol, cyclohexanediol, cyclohexanemethanediol, and mixtures thereof, of which 1,4-butanediol, 1,3-propanediol, and 1,2-ethanediol, and mixtures thereof, are particularly preferred. In a particularly preferred embodiment, the diol of the biodegradable polyester comprises at least 50 mole %, preferably at least 80 mole %, of 1,4-butanediol based on the total moles of diol.

[0022] The aliphatic aromatic polyesters are characterized by a polyfunctional aromatic acid content of 30 to 70 mole %, preferably 40 to 60 mole %, relative to the total molar content of dicarboxylic acids. Advantageously, branching compounds may be added to the aliphatic and aliphatic-aromatic polyesters in an amount of less than 0.5 mol %, preferably less than 0.2 mol %, relative to the total molar content of dicarboxylic acids, said branching compounds being selected from the group of polyfunctional molecules such as polyacids, polyols and mixtures thereof. Examples of polyacids include 1,1,2-ethanetricarboxylic acid, 1,1,2,2-ethanetetracarboxylic acid, 1,3,5-pentanetricarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, malic acid, citric acid, tartaric acid, 3-hydroxyglutaric acid, mucic acid, trihydroxyglutaric acid, hydroxyisophthalic acid, derivatives thereof, and mixtures thereof.

[0023] Examples of polyols are glycerol, hexanetriol, pentaerythritol, sorbitol, trimethylolethane, trimethylolpropane, mannitol, 1,2,4-butanetriol, xylitol, 1,1,4,4-tetrakis(hydroxymethyl)cyclohexane, arabitol, adonitol, iditol, and mixtures thereof. The aliphatic and aliphatic-aromatic polyesters may advantageously contain comonomers of hydroxy acid type in a percentage not exceeding 30 mol %, preferably not exceeding 20 mol %, relative to the total molar content of dicarboxylic acids, which may be present either in a random or block distribution of repeating units. Preferred hydroxy acids are D- and L-lactic acid, glycolic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid and octadecanoic acid. Hydroxy acids of the type having 3 or 4 carbon atoms in the main chain are preferred. Films containing anti-fog agents derived from blends of different polyesters are also included in the present invention.

[0024] In the sense of the present invention, biodegradable polyesters are understood to be polyesters which are biodegradable according to standard EN 13432. The polyesters used to manufacture the anti-fog films according to the invention, whether biodegradable or not, may be used in mixtures with one or more polymers of synthetic or natural origin, including those obtained by reactive extrusion processes. Preferably, the reactive extrusion process is carried out with the addition of a peroxide, epoxide or carbodiimide. Preferably, the reactive extrusion process is carried out using an amount of peroxide in the range of 0.001 to 0.2 wt. %, preferably 0.01 to 0.1 wt. %, relative to the total polymer fed to the reactive extrusion process.

[0025] As far as the addition of epoxides is concerned, these are preferably used in an amount of 0.1 to 2% by weight, more preferably 0.2 to 1% by weight of the total polymer fed to the reactive extrusion process. When carbodiimides are used, they are preferably used in an amount of 0.05 to 2% by weight, more preferably 0.1 to 1% by weight of the total polymer fed to the reactive extrusion process. Mixtures of these peroxides, epoxides and carbodiimides may also be used. Examples of peroxides which may be advantageously used are selected from the group consisting of dialkyl peroxides, such as benzoyl peroxide, lauroyl peroxide, isononanoyl peroxide, di(t-butylperoxyisopropyl)benzene, t-butyl peroxide, dicumyl peroxide, α,α'-di(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hex-3-yne, di(4-t-butylcyclohexyl)peroxydicarbonate, dicetyl peroxydicarbonate, dimyristyl peroxydicarbonate, 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane, di(2-ethylhexyl)peroxydicarbonate and mixtures thereof.

[0026] Examples of epoxides that can be advantageously used are all polyepoxides from epoxidized oils and / or styrene-glycidyl ether-methyl methacrylate, glycidyl ether-methyl methacrylate, having a molecular weight in the range of 1000 to 10000 and an epoxide number per molecule in the range of 1 to 30, preferably 5 to 25, as well as epoxides selected from the group comprising diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, 1,2-epoxybutane, polyglycerol polyglycidyl ether, isoprene diepoxide, and cycloaliphatic diepoxides, 1,4-cyclohexanedimethanol diglycidyl ether, glycidyl 2-methylphenyl ether, glycerol propoxylate triglycidyl ether, 1,4-butanediol diglycidyl ether, sorbitol polyglycidyl ether, glycerol diglycidyl ether, tetraglycidyl ether of meta-xylenediamine and diglycidyl ether of bisphenol A, and mixtures thereof. Catalysts can also be used to increase the reactivity of the reactive groups. In the case of polyepoxides, for example, salts of fatty acids may be used. Calcium stearate and zinc stearate are particularly preferred.

[0027] Examples of carbodiimides which may be advantageously used are poly(cyclooctylenecarbodiimide), poly(1,4-dimethylenecyclohexylenecarbodiimide), poly(cyclohexylenecarbodiimide), poly(ethylenecarbodiimide), poly(butylenecarbodiimide), poly(isobutylenecarbodiimide), poly(nonylenecarbodiimide), poly(dodecylenecarbodiimide), poly(neopentylenecarbodiimide), poly(1,4-dimethylenephenylenecarbodiimide), poly(2,2',6,6'-tetraisopropyldiphenylenecarbodiimide) (Stabaxol® D), poly(2,4,6-triisopropyl-1-phenylenecarbodiimide) (Stabaxol® P-100), poly(2,6-diisopropyl-1,3-phenylenecarbodiimide) ( Stabaxol® P), poly(tolylcarbodiimide), poly(4,4'-diphenylmethanecarbodiimide), poly(3,3'-dimethyl-4,4'-biphenylenecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(3,3'-dimethyl-4,4'-diphenylmethanecarbodiimide), poly(naphthylenecarbodiimide), poly(isophoronecarbodiimide), poly(cumenecarbodiimide), p-phenylenebis(ethylcarbodiimide), 1,6-hexamethylenebis(ethylcarbodiimide), 1,8-octamethylenebis(ethylcarbodiimide), 1,10-decamethylenebis(ethylcarbodiimide), 1,12-dodecamethylenebis(ethylcarbodiimide), and mixtures thereof.

[0028] In particular, the polyesters for the manufacture of the anti-fog films according to the invention may be used in mixtures with biodegradable polyesters of the dicarboxylic acid-diol type, the hydroxy acid type or the polyester-ether type. As far as the biodegradable polyesters of the dicarboxylic acid-diol type are concerned, they may be either aliphatic or aliphatic-aromatic. The biodegradable aliphatic polyesters from diacid-diols comprise aliphatic dicarboxylic acids and aliphatic diols, while the aromatic portion of the biodegradable aliphatic-aromatic polyesters consists mainly of polyfunctional aromatic acids of both synthetic and renewable origin, while the aliphatic portion consists of aliphatic dicarboxylic acids and aliphatic diols. Said biodegradable aliphatic-aromatic polyesters from diacid-diol are preferably characterized by an aromatic acid content of 30 to 90 mol %, preferably 45 to 70 mol %, relative to the acid component.

[0029] Preferably, the polyfunctional aromatic acids of synthetic origin are dicarboxylic aromatic compounds of the phthalic acid type and their esters, preferably terephthalic acid. The polyfunctional aromatic acids of renewable origin are preferably selected from the group comprising 2,5-furandicarboxylic acid and its esters. Particularly preferred are biodegradable aliphatic-aromatic polyesters from dicarboxylic acid-diols, in which the aromatic diacid component consists of a mixture of polyfunctional aromatic acids of synthetic and renewable origin. The aliphatic dicarboxylic acids of the biodegradable polyesters from dicarboxylic acid-diols are aliphatic dicarboxylic acids and their esters having 2 to 22 carbon atoms in the main chain. Dicarboxylic acids from renewable sources, their esters and mixtures thereof are preferred, among which adipic acid, pimelic acid, suberic acid, sebacic acid, azelaic acid, undecanedioic acid, dodecanedioic acid, brassylic acid and mixtures thereof are preferred.

[0030] Examples of aliphatic diols in the biodegradable polyesters from diacid-diols include 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, 2-methyl-1,3-propanediol, dianhydrosorbitol, dianhydromannitol, dianhydroiditol, cyclohexanediol, cyclohexanemethanediol, and mixtures thereof. Of these, 1,4-butanediol, 1,3-propanediol, and 1,2-ethanediol, and mixtures thereof, are particularly preferred. Preferably, the polyester mixtures for producing the anti-fog films according to the invention using biodegradable polyesters from the diacid-diols described above are characterized by a content of said biodegradable polyesters varying in the range of 5 to 95% by weight, more preferably 10 to 90% by weight, relative to the polyester (i).

[0031] The polyesters for producing the anti-fog films according to the invention may also be mixed with two or more aliphatic-aromatic polyesters having an aromatic moiety consisting primarily of polyfunctional aromatic acids or mixtures thereof, both of synthetic and renewable origin. With regard to the polyester mixture for producing the anti-fog film according to the present invention, preferred biodegradable polyesters from hydroxy acids include poly-L lactic acid, poly-D lactic acid and poly-LD lactic acid stereoisomer complexes, poly-ε-caprolactone, polyhydroxybutyrate, polyhydroxybutyrate-valerate, polyhydroxybutyrate-propanoate, polyhydroxybutyrate-hexanoate, polyhydroxybutyrate-decanoate, polyhydroxybutyrate-dodecanoate, polyhydroxybutyrate-octadecanoate, poly-3-hydroxybutyrate-4-hydroxybutyrate. Preferably, the polyester mixture for producing the anti-fog film according to the invention using the above biodegradable hydroxy acid polyester is characterized by a content of said biodegradable polyester varying in the range of 1 to 10% by weight, more preferably 1 to 5% by weight, relative to the polyester (i).

[0032] In a particularly preferred embodiment, the polyester for producing the anti-fog film according to the invention is mixed with 1 to 5% by weight of a polylactic acid polymer containing at least 75% of L-lactic acid or D-lactic acid or a mixture thereof and having a molecular weight Mw of more than 30,000. Said mixture is advantageously prepared by a reactive process for extruding the polyester according to the invention together with said polylactic acid polymer, preferably in the presence of an organic peroxide, such as those disclosed above. Polyesters may be used in mixtures with naturally occurring polymers such as starch, cellulose, chitin, chitosan, alginate, proteins such as gluten, zein, casein, collagen, gelatin, natural rubber, lignin itself or purified lignin, hydrolyzed lignin, basified lignin, or their derivatives. Starch and cellulose may be modified, including, for example, starch or cellulose esters with a substitution level of 0.2 to 2.5, hydroxypropylated starch, modified starches with fatty chains, and cellophane. Mixtures with starch are particularly preferred. Starch may also be used in unstructured, gelatinized, or filler form.

[0033] For the definition of "starch in unstructured form" according to the present invention, reference is made to the teachings of EP 0 118 240 and EP 327 505, according to which the starch is processed so that it does not substantially show so-called "Maltese crosses" in polarized light under an optical microscope and does not substantially show so-called "ghosts" in phase contrast under an optical microscope. The starch may constitute the continuous or dispersed phase, or may be in a co-continuous form. In the case of dispersed starch, the starch is preferably in a form having an average diameter of less than 1 μm, more preferably less than 0.5 μm. Preferably, the mixture of polyester and polymer of natural origin as defined above is characterized by a content of said polymer of natural origin varying between 1 and 30% by weight, more preferably between 2 and 15% by weight, relative to the polyester (i).

[0034] The polyesters for producing films containing the antifog agent according to the invention may be used in mixtures with polyolefins, non-biodegradable polyesters, polyether-urethanes, polyurethanes, polyamides, polyamino acids, polyethers, polyureas, polycarbonates and mixtures thereof. Preferred polyolefins are polyethylene, polypropylene, copolymers thereof, polyvinyl alcohol, polyvinyl acetate, polyethyl vinyl acetate and polyethylene vinyl alcohol. Among non-biodegradable polyesters, PET, PBT, and PTT are preferred, especially those with a renewable content of more than 30%, and polyalkylene furan dicarboxylates are preferred, among which polyethylene furan dicarboxylate, polypropylene furan dicarboxylate, polybutylene furan dicarboxylate, and mixtures thereof are particularly preferred.

[0035] Examples of polyamides are polyamides 6 and 6.6, polyamides 9 and 9.9, polyamides 10 and 10.10, polyamides 11 and 11.11, polyamides 12 and 12.12, and combinations thereof of the 6 / 9, 6 / 10, 6 / 11 and 6 / 12 types. The polycarbonate may be polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, mixtures and copolymers thereof. The polyether may be polyethylene glycol, polypropylene glycol, polybutylene glycol, copolymers thereof and mixtures thereof. Preferably, the mixtures of polyesters with the above-mentioned polymers (polyolefins, non-biodegradable polyesters, polyester- and polyether-urethanes, polyurethanes, polyamides, polyamino acids, polyethers, polyureas, polycarbonates and mixtures thereof) are characterized by a content of said polymer ranging from 0.5 to 99% by weight, more preferably from 5 to 50% by weight, relative to the polyester (i).

[0036] The process for producing the polyesters used to make the anti-fog films according to the present invention may be carried out according to any of the methods known in the art. In particular, polyesters can be advantageously obtained by polycondensation reaction. Advantageously, the polyester polymerization process can be carried out in the presence of a suitable catalyst. Suitable catalysts include, for example, organometallic tin compounds, such as stannic acid derivatives, titanium compounds, such as ortho-butyl titanate, aluminum compounds, such as Al-triisopropyl, or antimony and zinc compounds.

[0037] The content of terminal acid groups in the polyester used to prepare the anti-fog film according to the invention is preferably less than 100 meq / kg, preferably less than 60 meq / kg, even more preferably less than 40 meq / kg. The acid end group content may be measured as follows: 1.5-3 g of polyester is placed in a 100 ml conical flask with 60 ml of chloroform. After the polyester is completely dissolved, 25 ml of 2-propanol is added, followed by 1 ml of deionized water immediately before analysis. The resulting solution is titrated with a pre-standardized NaOH ethanol solution. The titration equivalence point is determined using an appropriate indicator, such as a glass electrode for acid-base titrations in non-aqueous solvents. The acid end group content is calculated from the amount of NaOH ethanol solution consumed according to the following formula:

[0038]

number

[0039] The present invention relates to films obtained from the biodegradable polyesters containing anti-fog agents and to methods for producing the films. The films have properties that make them suitable for many practical applications related to household and industrial consumption. Examples of such applications include food and non-food packaging, industrial packaging (e.g., pallets), agricultural packaging, and waste packaging. The film may also be advantageously produced by a film-blowing process, in which reels of monolayer film can be recovered downstream from the film-forming process by inflating a bubble, a feature that is particularly advantageous in terms of productivity of the manufacturing process.

[0040] Preferably, the bubble-blowing film-forming process is characterized by a blow-up ratio (BUR or transverse draw ratio) of 2 to 5 and a machine direction (MD) draw-down ratio (DDR or longitudinal draw ratio) of 5 to 60. In the sense of the present invention, DDR means a measure of the elongation of the melt exiting the extruder in the direction of draw, and BUR means the ratio of the bubble diameter to the die diameter. Advantageously, the process parameters are set during bubble blowing to have a DDR / BUR ratio of 3 to 15.

[0041] Processing aids may be added during the film-forming step without affecting the tackiness or transparency of the adhesive film according to the present invention. Such addition is carried out according to methods known to those skilled in the art. The process adjuvants are preferably fatty acid amides, such as stearamide, behenamide, erucamide, oleamide, ethylene bisstearamide, ethylene bisoleamide and derivatives, and antiblocking agents, such as silica, calcium carbonate, talc or kaolin. The film according to the present invention containing the anti-fogging agent has ultra-thin properties in the range of 3 to 50 μm, preferably 6 to 25 μm.

[0042] Films according to the invention exhibit strong adhesive properties both to themselves and to other non-adhesive surfaces such as ceramic, glass, metal, and plastics such as HDPE, LDPE, PP, PET, PVC. Furthermore, as a result of the chemical-physical properties of the biodegradable polyesters used, adhesive films obtained from said polyesters can be produced without the use of plasticizers or adhesives (known as tackifiers), such as polyisobutene or ethylene vinyl acetate, which makes it possible to understand a further significant difference between the films according to the invention and PVC and polyethylene adhesive films, whose use in the food packaging sector is severely limited due to the presence of the aforementioned additives. In a particularly preferred embodiment, the film according to the present invention is substantially free of plasticizers and adhesives.

[0043] The films also have excellent mechanical properties, with a particular combination of tearability, strength and stretchability making them particularly suitable for use in industrial and food packaging. Preferably, the film has an elongation at break of greater than 350%, a modulus of elasticity greater than 70 MPa and a load at break of greater than 30 MPa in the transverse direction relative to the film formation direction, and an elongation at break of greater than 300%, a modulus of elasticity greater than 80 MPa and a load at break of greater than 35 MPa in the longitudinal direction relative to the film formation direction. More preferably, the film has an elongation at break of greater than 400%, a modulus of elasticity greater than 90 MPa and a load at break of greater than 40 MPa in the transverse direction relative to the film formation direction, and an elongation at break of greater than 350%, a modulus of elasticity greater than 100 MPa and a load at break of greater than 45 MPa in the longitudinal direction relative to the film formation direction. As far as the mechanical properties are concerned, in the sense of the present invention, these are determined in accordance with ASTM D882 (traction force at 23° C. and 55% relative humidity and v0=50 mm / min).

[0044] The film is characterized by a maximum puncture resistance of greater than 15 N, preferably greater than 20 N, as determined by ASTM D5748 (Standard Test Method for Protrusion Puncture Resistance of Stretch Wrap Film). The film is advantageously characterized by excellent optical properties. In particular, it preferably has a haze value of less than 20%, preferably less than 15%, even more preferably less than 10%, and a transmittance value of more than 80%, preferably more than 90%, thereby allowing the user to identify an object packaged therein without having to unwrap the object. This feature is extremely advantageous when used for food packaging. The optical properties are determined in accordance with ASTM D1003. Films having compositions including biodegradable hydroxy acid polyesters (eg, PLA) have increased modulus, reduced tack, and improved unwindability at the expense of clarity.

[0045] In addition to the above-mentioned properties, the film obtained according to the invention advantageously has a water vapor permeability much higher than that of PVC and PE films. In particular, it preferably has a water vapor permeability of 200 g / m 2 measured at 23° C. and 50% RH on a 16 μm thick film. 2 / day, preferably 300-900g / m 2 / day WVTR (water vapor transmission rate). Water vapor transmission properties are determined in accordance with ASTM F1249. Biodegradable packaging films according to the invention mean films that are biodegradable and compostable according to standard EN 13432. The film antifogging agent according to the present invention is a compound consisting of molecules with polar and non-polar parts, like soaps and emulsifiers. In this molecule, the non-polar parts generally adhere to the film, while the polar groups increase the polarity of the film surface. This has the effect of dispersing and removing water droplets (they appear as an additional water layer on the film). Therefore, it is particularly surprising that this additional antifogging agent layer has the effect of increasing the transparency (especially haze) of the film compared to the same film made from the same biodegradable polyester, except that it does not contain the antifogging agent.

[0046] A further surprising advantage that overcomes preconceived notions in the art is that films according to the present invention in the presence of an anti-fog agent exhibit superior behavior on packaging machines. In particular, it has been confirmed that current packaging machines can package 80 to 90 packages per minute using the film according to the present invention. Regarding the mechanical properties under natural aging conditions, the film still exhibits good toughness even after 6 months of the film formation process. In particular, with regard to mechanical properties under natural aging conditions, after 6 months of the film formation process, the films exhibited excellent mechanical properties in terms of load at break (determined according to ASTM D882 at 23°C, 55% relative humidity and v = 50 mm / min) and puncture resistance of stretch films under biaxial stress (expressed as force at break (N) and determined according to ASTM D5748 at 23°C, 55% relative humidity and v = 50 mm / min). o = 250 mm / min) does not decrease by more than 35%, preferably by more than 25%. Films according to the invention are particularly suitable for food packaging, industrial packaging, agricultural baling, and waste packaging. [Example]

[0047] Example 1 - Preparation of biodegradable polyester, description of anti-fog agent used, and table of compositions used P1: Poly(1,4-butylene adipate-co-1,4-butylene terephthalate) [PBAT], with a terephthalic acid content of 47 mol% based on the total dicarboxylic acid content. This PBAT has a MFR of 4.1 g / 10 min (@190°C, 2.16 kg), a shear viscosity of 1304 Pas at 180°C, a melt strength of 1.0 g, and a terminal acid group content of 38 meq / kg. P2: Poly(1,4-butylene adipate-co-1,4-butylene azelate-co-1,4-butylene terephthalate) [PBATAz], with a terephthalic acid content of 47 mol% based on the total dicarboxylic acid content. PBATAz has a MFR of 4.9 g / 10 min (@190°C, 2.16 kg), a shear viscosity of 1178 Pas at 180°C, a melt strength of 1.1 g, and a terminal acid group content of 34 meq / kg.

[0048] PLA: Ingeo 3251D polylactic acid has a MFR of 35g / 10min (@190°C, 2.16kg) and M W =105000. P3: Poly(1,4-butylene adipate-co-1,4-butylene terephthalate) [PBAT], with a terephthalic acid content of 47 mol% based on the total dicarboxylic acid content. This PBAT has a MFR of 4.2 g / 10 min (@190°C, 2.16 kg), a shear viscosity of 1289 Pas at 180°C, a melt strength of 0.9 g, and a terminal acid group content of 33 meq / kg. A1: Sabo polyglycerol laurate anti-fog agent A2: Sorbitan polyoxyethylene monolaurate ester manufactured by Croda AC: Sorbitan monostearate anti-fog agent manufactured by Sabo S: HMV-5CA-LC hydrolysis stabilizer

[0049] [Table 1]

[0050] The different compositions were fed into a model OMC EBV60 / 36 twin screw extruder operating under the following conditions: Screw diameter (D) = 58 mm; L / D=36; Screw rotation = 140 rpm; Temperature profile = 60-150-180-190 × 4-150 × 2 °C; Throughput: 40 kg / h; Vacuum degassing in zone 8 of 10

[0051] The granules thus obtained were fed into a Ghioldi model blown film machine having a screw diameter of 40 mm and L / D of 30, operating at 30 rpm. The air gap of the film-forming head was 0.9 mm, and L / D was 12. 18 μm thick (9 + 9) films [Examples 1, 2, 4, 6-10] and 20 μm thick (10 + 10) films [Examples 3, 5] were obtained using the conditions listed in Table 2.

[0052] [Table 2]

[0053] Three grams of film were analyzed to determine the weight percentage ("q") of polyester oligomers having an average molecular weight of ≦10,000 using the method described herein. The film was analyzed by gel permeation chromatography (GPC). Measurements were performed at 40° C. using an Agilent® 1100 chromatograph. Measurements were performed using a set of two columns in series (5 μm and 3 μm particle diameters with mixed porosity), a refractive index detector, chloroform as the eluent (flow rate 0.5 ml / min), and polystyrene as the reference standard.

[0054] [Table 3]

[0055] Mechanical properties were determined according to ASTM D882 (tensile strength at 23°C and 55% relative humidity and v0 = 50 mm / min). Optical properties were determined according to ASTM D1003. Water vapor permeability was determined at 23°C and 50% relative humidity using ASTM F1249. A cold fog test was conducted to evaluate the performance of the anti-fog agent. 200 ml of water at 30°C was poured into a 250 ml beaker. After attaching the test film to the beaker, the sample was placed in a refrigerator at 4°C. The changes in the film surface regarding the formation of a water layer were recorded, and the beaker was removed from the refrigerator and observed after 5 minutes, 15 minutes, 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 1 day, 2 days, 3 days, 4 days, and 6 days. The time when the transition from a water droplet layer to a discontinuous water film occurs is used as an indicator of the effectiveness of the anti-fog agent.

[0056] Example 2: Comparison of experimental data [Table 4]

[0057] Key points from Table 4: The term "stickiness" according to the present invention defines the ability of a film to adhere to itself and to surfaces on a scale of 1 (low) to 5 (high). The term "unwindability" according to the present invention is understood as the ease with which the film can be unwound on a scale of 1 (low) to 5 (high).

[0058] [Table 5]

[0059] Key points from Table 5: The term "stickiness" according to the present invention defines the ability of a film to adhere to itself and to surfaces on a scale of 1 (low) to 5 (high). The term "unwindability" according to the present invention is understood as the ease with which the film can be unwound on a scale of 1 (low) to 5 (high).

[0060] [Table 6]

[0061] As can be seen from the table, the high water vapor barrier (WVTR = 170 g / m) in Comparative Example 6 2 / day) confirms that excessive addition of anti-fog agent to the surface does not impart anti-fog properties but leads to a degradation of optical properties compared to the reference.

[0062] [Table 7]

[0063] Example 3: Film performance in food tray packaging equipment Films prepared according to Example 1 (Composition 1) were tested using an OMORI STN 8500 WE® food tray packaging machine. The film had a nominal thickness of 16-18 microns - 400 mm reel strip, and the trays used were PS with a short side length of 360 mm. The packaging process was divided into three stages. 1. Wrap the tray, weld it in the middle, and cut it into a cylindrical shape; 2. Fold the tip and tail of the tube under the tray; 3. The product is transported on a heated belt and the folded section is welded.

[0064] In the first stage, the film showed good mechanical behavior (good elasticity) both during the transport and conveying stage and during the central sealing stage, which was performed by two pairs of heated rollers (set at 135°C). No problems were observed during the cutting stage. In the second stage, the temperature of the glass fiber belt was set at 150°C and operated at a high wrapping speed, increasing from 35 trays / min to 80-90 trays / min, so that the fold was properly folded at the bottom of the tray. No significant problems were identified during the transport and welding stage on the heated belt (stage 3).

Claims

1. (i) having a melt strength of 0.7 to 4 g and containing at least one dicarboxylic acid unit and at least one diol unit; M n ≧40000 M w / q≦90000 A biodegradable polymer having the formula: Melt strength is measured according to ISO 16790:2005 at 180°C and γ = 103.7s -1 6 mm / s using a capillary with a diameter of 1 mm and L / D = 30 2 Measured at a constant acceleration of 110 mm and an extension length of 110 mm. Molecular weight “M n " and "M w " is determined by gel permeation chromatography (GPC); "q" = a biodegradable polymer, which is the weight percentage of polyester oligomers having a molecular weight by GPC of 10,000 or less; (ii) an anti-fog agent selected from esters of polyfunctional alcohols (provided that the esters are not stearates), preferably condensation products of polyfunctional alcohols with one or more fatty acids, and ethoxylated derivatives thereof; A packaging film having a coefficient of static friction (COF) greater than 5, comprising:

2. 2. Packaging film according to claim 1 for the production of thin films with a thickness of 3 to 50 μm, preferably 6 to 25 μm.

3. 2. Packaging film according to claim 1, wherein the anti-fog agent is present in an amount of 0.2 to 5%, preferably 1 to 3%, based on the polyester content.

4. 2. The packaging film of claim 1, wherein the anti-fog agent is present in an amount of 1.0 to 2.0%, more preferably 1.0 to 1.5%, based on the polyester content.

5. 2. The packaging film of claim 1, wherein the anti-fog agent is selected from esters of fatty acids having 8 to 18 carbon atoms.

6. 10. The packaging film of claim 1, wherein the anti-fog agent is selected from polyglyceryl laurate and sorbitan monolaurate.

7. 10. The packaging film of claim 1, wherein the anti-fog agent is a sorbitan polyoxyethylene monolaurate ester.

8. 10. The packaging film of claim 1, wherein the anti-fog agent is added to the polyester directly by an extrusion process to a desired final concentration or in the form of a "masterbatch" during the film-forming step in a hopper.

9. 9. The packaging film according to claim 1, wherein the biodegradable polyester (i) has an aromatic component comprising at least one polyfunctional aromatic acid and an aliphatic component comprising at least one aliphatic diacid and at least one aliphatic diol.

10. 10. Packaging film according to any one or more of the preceding claims, wherein the biodegradable polyester (i) comprises biodegradable aliphatic-aromatic polyesters and aliphatic polyesters.

11. 10. The packaging film according to claim 9, wherein the polyfunctional aromatic acid is selected from aromatic dicarboxylic acid compounds of the phthalic acid type and heteroaromatic dicarboxylic acid compounds of renewable origin and their esters and mixtures thereof.

12. 12. The packaging film according to claim 1, wherein in the biodegradable polyester (i), the dicarboxylic acids comprise acids selected from azelaic acid, sebacic acid, adipic acid or mixtures thereof in an amount of at least 50 mol % of the total moles of aliphatic dicarboxylic acids.

13. Packaging film according to any one or more of the preceding claims, wherein the biodegradable polyester (i) is mixed with one or more polymers of synthetic or natural origin.

14. 14. The packaging film of claim 13, wherein the polymer of synthetic or natural origin is biodegradable.

15. 14. The packaging film of claim 13, wherein the biodegradable polyester (i) is mixed with poly-L-lactic acid, poly-D-lactic acid and poly-LD-lactic acid stereoisomer complexes, poly-ε-caprolactone, polyhydroxybutyrate, polyhydroxybutyrate-valerate, polyhydroxybutyrate-propanoate, polyhydroxybutyrate-hexanoate, polyhydroxybutyrate-decanoate, polyhydroxybutyrate-dodecanoate, polyhydroxybutyrate-octadecanoate, poly-3-hydroxybutyrate-4-hydroxybutyrate.

16. 14. The packaging film of claim 13, wherein the biodegradable polyester (i) is mixed with 1 to 5% by weight of a polylactic acid polymer containing at least 75% of L-lactic acid or D-lactic acid or a mixture thereof and having a molecular weight Mw of more than 30,000.

17. Packaging film according to any one of claims 1 to 16 for food packaging, industrial packaging, agricultural baling or waste packaging.

18. 10. The use of an antifogging agent selected from esters of polyfunctional alcohols (provided that the esters are not stearates), preferably condensation products of polyfunctional alcohols with fatty acids, in a mixture with the biodegradable polyester according to claim 1, for the production of thin films having a thickness of 3 to 50 μm, preferably 6 to 25 μm.